Penggunaan School Management System EdConnect untuk Kinerja Pengguna Di Tinjau Dari Aspek Kualitas, Efektivitas dan Ketepatan Waktu di Sekolah XYZ - Lie Risky Ferdinan; Yohana Novi Indriani; Chatarina Yuniarawati; Sri Murniati (Magister Teknologi Pendidikan Fakultas Pascasarjana Pendidikan Universitas Pelita Harapan, 2025)
Technological advancements have prompted XYZ School to enhance the quality of its educational offerings. A significant initiative undertaken is the implementation of the EdConnect School Management System, which aims to bolster administrative efficiency, refine academic processes, and expedite access to information for educators and school personnel. The objective of this study is to examine the impact of the EdConnect School Management System's implementation on the quality, effectiveness, and punctuality of its users' performance at XYZ School. This investigation employs a quantitative methodology, utilizing data collection techniques via questionnaires completed by 44 participants, comprising educators and school staff who utilize the system. The data were analyzed using simple linear regression analysis. The result indicate that the use of Edconnect has a positive and significant effect on user performance, with a regression coefficient of 0,928 and a coefficient of determination ( R2 ) of 0.964. These findings demonstarate that the optimal utilization of school management information system plays a crucial role in improving work quality, effectiveness and timeliness of users.